A scientometrics analysis and visualization of low back pain. (March 2023) - Zuo, Yongli; Zhang, Juntao; Leng, Xiangyang; Fan, Yihua; Fu, Bifeng; Wang, Ping
Abstract: Background: Although low back pain (LBP) contributes to the global disease burden, literature on the scientometric analysis of low back pain is limited. Objective: This study aimed to demonstrate the research state and capture developmental dynamics of low back pain utilizing scientometric analysis and visualization methods. Methods: Literature on low back pain from 2011 to 2020 was retrieved from the Web of Science core collection. CiteSpace software was used to generate the relevant knowledge map and carry out scientometric analysis on the volume of literature, cooperation between countries/regions and research institutions, disciplines, journals, highly cited references, and keywords. Research hotspots and trends of the included literature were then stated. Results: A total of 27, 968 publications were obtained and the number of annual publications maintained growth continually. Australia and the University of Washington had the maximum centrality. The USA and the University of Sydney were the most prolific country and institution respectively, thus indicating that they are important in this field. Publications were devoted to the disciplines of neurology, orthopedics and rehabilitation. The highest cited journal is Spine (18478), followed by European Spine Journal (11344) and Pain (11097). The systematic review, disease burden, epidemiology, clinical practice recommendations, and primary care management are the key subjects covered by highly cited papers. The keywords were primarily concerned with pain etiology, disease type, clinical treatment, and trials. Burst keywords in LBP were controlled trial, practice guideline, stability, adolescent, individual, activation and expression, which can be regarded as research hotspots and frontiers. Conclusion: In conclusion, the data clearly shows a consistent increase in LBP studies. The historical review provides insight into LBP as well as valuable information for researchers to identify new perspectives on potential cooperative institutions, hot topics, and a strong foundation for future research.